Identifikasi Bakteri Mycobacteriumtuberculosis dengan Metode TCM (Tes Cepat Molekuler) pada Pasien Suspek di RSUD Palembang Bari Provinsi Sumatera Selatan - Muslimin Muslimin; Rahayu Rahayu; Minarti Minarti; Ali Zainal Abidin (KOLONI, 2026)
Tuberculosis (TB) is an infectious disease that remains a serious public health problem worldwide. The disease is caused by Mycobacterium tuberculosis and can spread through the air when infected individuals cough, sneeze, spit, or speak. Because transmission occurs easily, early diagnosis and rapid treatment are essential to reduce morbidity and mortality rates. The purpose of this examination was to detect Mycobacterium tuberculosis in suspected TB patients at Palembang BARI Regional General Hospital. The examination used the Molecular Rapid Test (TCM) with the GeneXpert instrument. This method is a semi quantitative Real Time Polymerase Chain Reaction Assay (RT-PCR) designed to identify Mycobacterium tuberculosis DNA quickly, automatically, and accurately using a single use cartridge. The TCM method offers several advantages, including a short examination time of approximately two hours and the ability to detect at least 131 bacteria per milliliter of sputum sample. Results from 13 respondents showed that 6 samples were positive (MTB detected), 6 samples were negative (MTB not detected), and 1 sample was indeterminate. Based on these findings, the TCM examination demonstrated higher sensitivity and specificity than conventional diagnostic methods for detecting tuberculosis effectively and accurately. Furthermore, the TCM method helps healthcare workers determine appropriate treatment rapidly, allowing patients to receive management and reducing the risk of disease transmission within the community. Therefore, the use of GeneXpert technology is expected to support tuberculosis control and prevention programs in Indonesia.